Study of Pattern of Fusion of Coronal Suture Using Skull Radiography and its Association with Documented Age in Males - Ishita Thakur1 , Rashid Nehal Khan2 , Thippesh Kumar3 , Abhijit Rudra3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cases of age estimation are seen by Forensic Practitioners. Identification is the establishment of theindividuality of a person. A medico-legal dispute can arise at any age. Age estimation is needed to applyfor government posts or pension or in cases of amnesia. Legal enforcement agencies often bring casesfor estimation of age, a few examples are that for employment, superannuation, pension settlements andbenefits. Use of fusion of sutures on the skull with other factors has been found reliable for age estimation.In the present study we studied skull roentgenogram of patients. These patients were advised roentgenogramfor diagnostic and therapeutic purpose from other clinical departments. We studied the stage of fusion ofcoronal sutures in those roentgenograms where age of the patient was documented after verification againsta standard identity proof. The suture was divided into upper half and lower half and stage of fusion wasdocumented. We followed the Key stage of fusion of sutures. The earliest age of commencement of suturefusion was at 34 years and 30 years in its upper half and lower half respectively in our study. The earliest ageof completion of suture fusion was 56 years in upper half and 50 years at lower half.